Integration of new biological and physical retrospective dosimetry methods into EU emergency response plans – joint RENEB and EURADOS inter-laboratory comparisons. (2nd January 2017) - Ainsbury, Elizabeth; Badie, Christophe; Barnard, Stephen; Manning, Grainne; Moquet, Jayne; Abend, Michael; Antunes, Ana Catarina; Barrios, Lleonard; Bassinet, Celine; Beinke, Christina; Bortolin, Emanuela; Bossin, Lily; et al.
Abstract: Purpose: RENEB, 'Realising the European Network of Biodosimetry and Physical Retrospective Dosimetry, ' is a network for research and emergency response mutual assistance in biodosimetry within the EU. Within this extremely active network, a number of new dosimetry methods have recently been proposed or developed. There is a requirement to test and/or validate these candidate techniques and inter-comparison exercises are a well-established method for such validation. Materials and methods: The authors present details of inter-comparisons of four such new methods: dicentric chromosome analysis including telomere and centromere staining; the gene expression assay carried out in whole blood; Raman spectroscopy on blood lymphocytes, and detection of radiation-induced thermoluminescent signals in glass screens taken from mobile phones. Results: In general the results show good agreement between the laboratories and methods within the expected levels of uncertainty, and thus demonstrate that there is a lot of potential for each of the candidate techniques. Conclusions: Further work is required before the new methods can be included within the suite of reliable dosimetry methods for use by RENEB partners and others in routine and emergency response scenarios.